Synergistic antimicrobial potential of EGCG and fosfomycin against biofilms associated with endodontic infections - Duque, Cristiane [UNESP]; Souza, Amanda Caselato Andolfatto [UNESP]; Aida, Kelly Limi [UNESP]; Pereira, Jesse Augusto [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Dos Santos, Vanessa Rodrigues [UNESP]; Cosme-Silva, Leopoldo; Prakki, Anuradha (FapUNIFESP (SciELO), 2023)
Objective: This study aimed to evaluate the cytotoxicity and synergistic effect of epigallocatechin gallate (EGCG) and fosfomycin (FOSFO) on biofilms of oral bacteria associated with endodontic infections. Methodology: This study determined minimum inhibitory and bactericidal concentration (MIC/ MBC) and fractionated inhibitory concentration (FIC) of EGCG and FOSFO against Enterococcus faecalis, Actinomyces israelii, Streptococcus mutans, and Fusobacterium nucleatum. Monospecies and multispecies biofilms with those bacteria formed in polystyrene microplates and in radicular dentin blocks of bovine teeth were treated with the compounds and control chlorhexidine (CHX) and evaluated by bacterial counts and microscopy analysis. Toxicity effect of the compounds was determined on fibroblasts culture by methyl tetrazolium assays. Results: The combination of EGCG + FOSFO demonstrated synergism against all bacterial species, with an FIC index ranging from 0.35 to 0.5. At the MIC/FIC concentrations, EGCG, FOSFO, and EGCG+FOSFO were not toxic to fibroblasts. EGCG+FOSFO significantly reduced monospecies biofilms of E. faecalis and A. israelli, whereas S. mutans and F. nucleatum biofilms were eliminated by all compounds. Scanning electron microscopy of multispecies biofilms treated with EGCG, EGCG+FOSFO, and CHX at 100x MIC showed evident biofilm disorganization and substantial reduction of extracellular matrix. Confocal microscopy observed a significant reduction of multispecies biofilms formed in dentin tubules with 84.85%, 78.49%, and 50.6% of dead cells for EGCG+FOSFO, EGCG, and CHX at 100x MIC, respectively. Conclusion: EGCG and fosfomycin showed a synergistic effect against biofilms of oral pathogens related to root canal infections without causing cytotoxicity.
Keywords: Biofilms; Cytotoxicity tests; Drug synergism; Epigallocatechin gallate; Fosfomycin